Influence of Cement Thickness on the Polymerization Shrinkage Stress of Adhesively Cemented Composite Inlays: Photoelastic and Finite Element Analysis - Larissa Mendes Campaner; Alana Barbosa Alves Pinto; Amir Mohidin Demachkia; Tarcísio José de Arruda Paes-Junior; Clóvis Pagani; Alexandre Luiz Souto Borges (MDPI AG, 2021)
The objective of this study was to analyze the effect of cement thickness on the strain and stresses resulting from the polymerization of resin cement using photoelasticity and Finite Element Analysis (FEA). For this study, twenty upper first premolars with inlay cavity preparation were constructed from photoelastic resin and restored with composite resin inlay. The samples were divided into two groups (n = 10) according to the film thickness of resin cement material. For Group 1, the film thickness was 100 μm; for Group 2, the film thickness was 400 μm. After polymerization of the cement, photoelastic analysis and finite element analysis (FEA) were performed. In the photoelastic analysis, Group 2 showed higher strain with the presence of second-order fringe even after 24 h. In Group 1, the formation of first order fringes was not observed, even after 24 h. In the FEA analysis, the greatest cusp deflection and tensile stress occurred in Group 2 (0.00026 mm and 0.305 MPa, respectively) due to the polymerization shrinkage in the lingual cusp compared to Group 1 (0.000107 mm and 0.210 MPa, respectively). It can be concluded that the thickness of the resin cement influences the cusp deflection, with the greater thickness of the cement layer, the greater stresses and deformations in the tooth structure occur.